Beyond Formal Accountability: A Prophetic Social Science Perspective on Waqf Governance - Nurngaini, Siti; Sholihin, Mahfud; Fatmawati, Dewi (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2026)
This study critically examines the practices and underlying dynamics of accountability within a waqf management institution by exploring how accountability is constructed, enacted, and experienced through the lens of Kuntowijoyo’s Prophetic Social Science. Adopting a qualitative case study approach, the research focuses on the Sultan Agung Waqf Foundation in Semarang, Indonesia. Data were collected through in-depth interviews, observations, and document analysis, and subsequently analyzed using thematic analysis guided by Kuntowijoyo’s framework of Prophetic Social Science. The findings reveal that accountability within the institution extends beyond administrative and legal-formal dimensions, encompassing the values of humanization, liberation, and transcendence. It suggests that accountability in waqf institutions is not merely procedural but reflects a form of prophetic practice oriented toward social welfare and spiritual responsibility. This study contributes to the literature on Islamic accountability by illustrating how prophetic values can be operationalized within waqf governance, offering a more holistic and value-driven perspective. Practically, the findings suggest that waqf managers should integrate ethical and spiritual values into formal accountability systems to enhance transparency, social impact, and long-term sustainability.